Gambaran Kepatuhan dan Self Management pada Pasien Gagal Ginjal Kronik: LIterature Review - Nabila Fitriani; Liza Fitri Lina; Eva Oktavidiati; Weti (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Chronic Kidney Disease (CKD) is a chronic health problem whose prevalence continues to increase globally, including in Indonesia. This condition is progressive and requires long-term therapy such as dietary management, fluid restriction, regular medication adherence, and dialysis therapy. The purpose of this study was to describe CKD patient adherence to dietary and self-management practices based on a literature review. The method used in this study was a narrative literature review, a type of literature review that collects and synthesizes information from various scientific journals descriptively. The search results were analyzed using the PICO method. The review results showed that CKD patient adherence to fluid and dietary restrictions improved significantly after receiving health education. Health education and family support play a crucial role in encouraging adherence, while the duration of hemodialysis also influences patient adherence. CKD patient self-management is improved through health education and dietary counseling. Good knowledge encourages proactive behavior, adherence to therapy, and improves patient quality of life, self-confidence, and independence, especially for patients undergoing long-term hemodialysis. Overall, health education, family support, and patient experience in undergoing hemodialysis therapy are the main factors that influence compliance and self-management practices of CKD patients.